Production of cyclodextrin glucanotransferase (CGTase) from Bacillus sp. TS1-1: process optimisation - Ahmad Tarmizi, Azmil Haizam; Md. Illias, Rosli; Md. Salleh, Madihah; Hassan, Osman; Kamaruddin, Kamarulzaman; Abdul Rahman, Roshanida; Abdul Aziz, Suriani (Universiti Malaysia Sabah, 2003)
The effect of pH and temperature were investigated for an optimized condition of cyclodextrin glucanotransferase (CGTase) production from Bacillus sp. TS1-1. The optimization process was analysed using Central Composite Experimental Design in Response Surface Methodology (RSM) by Design Expert Version 6.0.4 (StatEase, USA). This design was employed to derive a statistical model for the effects of pH and temperature on the production of CGTase from Bacillus sp. TS1-1. The coefficient of determination, R2 was found to be 97.85%. The temperature of 29.59C and the pH of 10.32 had been found to be the optimum conditions for the maximum production of CGTase after 24 hr of incubation. In these conditions, the CGTase activity was attained to be 75.48 U/ml, which was close to the model predictions.